Brújula Intersexual: Working Strategies, the Emergence of the Mexican Intersex Community, and Its Relationship with the Intersex Movement - Eva Alcántara; Laura Inter; Frida Flores; Carlos Narváez-Pichardo (Social Sciences, 2024)
After a decade of work, Brújula Intersexual has become a reference in Mexico and Latin America. However, the presence of the Latin American intersex movement in the specialised literature in English is restricted. We consider that conducting a self-reflexive review of Brújula Intersexual could contribute to understanding (1) the work strategies implemented by Brújula Intersexual; (2) the formation of the Spanish-speaking intersex community and movement in Mexico; and (3) the heterogeneous dynamics of the global intersex movement. We designed a qualitative–quantitative study involving discussion meetings with the Brújula Intersexual team, revision of the Brújula Intersexual archive, a scoping review, and a timeline. The results and discussion are focused on two axes: (1) Brújula Intersexual: structure and working strategies, in which two concepts are developed, namely, the intimate sphere and the atmosphere of trust; (2) The articulation of Brújula Intersexual within the intersex movement and its resonances in public policy. Researching Brújula Intersexual contributes to the collective memory and reveals important events that link the Spanish-speaking and global anglophone intersex movements. In particular, Brújula Intersexual was configured as a critical counter-device that manages intense flows of affection, allowing for the production of new subjectivation modes for people with intersex bodies.